Dietary fiber and probiotics based on gut microbiota targeting for functional constipation in children with cerebral palsy - Huang, Congfu; Lyu, Jinli; Chu, Chunuo; Ge, Lan; Peng, Yuanping; Yang, Zhenyu; Xiong, Shenghua; Wu, Bin; Chen, Xiao; Zhang, Xiaowei (Frontiers in Pediatrics, 2022)
Gastrointestinal (GI) disorders are very common among children with cerebral palsy. Gut microbiota has been confirmed to maintain normal GI physiological function and further contributed to cerebral palsy through the gut-brain axis. Our study was to investigate the effect of dietary fiber combined with probiotics on functional constipated children with cerebral palsy. In total, 35 patient children were enrolled and divided into general diet group (n = 14) and liquid diet group (n = 21). All the participants received Compound Dietary Fiber (CDF) for 1 month and lactic acid-producing and butyric acid-producing probiotics for 6 months. After a 1-month intervention, the frequency of spontaneous and manual defecation, and Bristol score were all significantly improved (P < 0.001). The α-diversity of the gut microbiota was significantly increased after a 1-month intervention (P < 0.05), with a higher abundance of butyric acid-producing bacteria and a lower abundance of opportunistic pathogens (P < 0.05, FDR < 0.05). However, the impersistent effect of the 6-month intervention suggested the insufficient impact of intaking probiotics alone and the short duration of CDF intervention. Moreover, although the intervention had affected the constipation symptoms equally in cerebral palsy children with a general diet and liquid diet, the general diet group showed a greater and more durable change in gut microbiota and clinical phenotypes after intervention than the liquid diet group, which indicated that longer intervention time should be considered for liquid diet children. This study not only illustrated that supplementation of dietary fiber combined with probiotics can improve functional constipation in children with cerebral palsy, but also provides guidance for optimal intervention strategy for future studies, which will further benefit cerebral palsy children. Clinical trial registration: http://www.chictr.org.cn/showproj.aspx?proj=46902, identifier: ChiCTR1900028257.